(untitled) (Sport Science Research, 2025)
The article examines the possibilities of using artificial intelligence (AI) ChatGPT to assess the physical fitness of students with hearing impairments. Attention is paid to the development and testing of AI algorithms capable of considering the characteristics of this category of students in order to increase the accuracy of diagnosing their physical capabilities. Comparative analysis of the effectiveness of traditional AI methods and technologies among students of 1-3 courses in the specialty 6B01401 “Physical culture and sports” - NAO “Shakarim University of Semey”. The results of a study among students of 1-3 courses in the specialty 6B01401 “Physical Culture and Sports” of the NAO “Shakarim University of Semey” demonstrate the prospects of using AI to develop individualized physical activity programs adapted to the specific needs of students with hearing impairments, which opens up new opportunities in the field of inclusive education and sports, as well as helps specialists in training and the development of adaptive physical activity programs. To achieve the best results, it is necessary to apply an integrated approach that includes regular physical exercises, and work with teachers and psychologists aimed at developing sensory skills. For diagnosis, the indicator of physical fitness of students before and after the introduction of AI was used among students of 1-3 courses in the specialty 6B01401 “Physical culture and sports” of the NAO “Shakarim University of Semey” with hearing impairments.